Influence of smoking on levels of urinary 8-iso Prostaglandin F2α. (2019) - van der Plas, Angela; Pouly, Sandrine; de La Bourdonnaye, Guillaume; Baker, Gizelle; Lüdicke, Frank
Highlights: Cigarette smoking is an important modifiable risk factor for cardiovascular disease. Cigarette smoking affects oxidative stress markers such as 8-iso prostaglandin F2α. The effect of smoking on urinary 8-iso prostaglandin F2α levels was meta-analyzed. Urinary 8-iso prostaglandin F2α levels were increased in smokers. Abstract: Background: To evaluate the reduced-risk potential of alternative tobacco products, biomarkers that are involved in the biological pathways affected by cigarette smoking and smoking cessation are needed. Isoprostanes, a measure of oxidative stress, appear to be influenced by smoking and reversible upon smoking cessation and therefore could be a good biomarker. This review aims at quantifying the effect of smoking and smoking cessation on levels of urinary 8-iso prostaglandin F2α (8-epi-PGF2α ), an isoprostane. Methods: PubMed and Scopus databases were searched for publications that reported 8-epi-PGF2α levels in smokers and nonsmokers as well as articles reporting the effect of smoking cessation on 8-epi-PGF2α levels. Results: Eighteen studies assessing 8-epi-PGF2α levels by smoking status were identified. Five of the papers reported the results as quantity excreted in 24-hour urine (μg/24 h), and 15 reported creatinine adjusted values. The meta-analyses show increased levels of 8-epi-PGF2α in current smokers compared with nonsmokers (mean difference = 0.16, 95% confidence interval [95%CI]: 0.14–0.19 μg/24 h with inconsistency statistic [I 2 ] = 98%; mean difference = 172.38, 95%CI: 152.75–192.01 pg/mg creatinine with I 2  = 89%, respectively). There were too few publications to perform a meta-analysis assessing the effects of smoking cessation on 8-epi-PGF2α levels. Conclusions: Due to the high heterogeneity among the studies included in these meta-analyses, it is difficult to generalize the results; however, our study indicates increased levels of 8-epi-PGF2α and therefore increased oxidative stress in smokers compared with nonsmokers. More studies are still needed to assess if 8-epi-PGF2α levels are reversible after cessation.